Midwifery Practices in Promoting Maternal and Neonatal Health - Anita, Nur (Advances in Healthcare Research, 2024)
Purpose: This study aims to explore the role of midwifery practices in promoting maternal and neonatal health, with a focus on the impact of midwifery-led care models, cultural competence, and the integration of midwifery into national health systems. Research Design and Methodology: The research employs a qualitative design, utilizing semi-structured interviews and focus group discussions with midwives, healthcare providers, policymakers, and community health workers in low-resource settings. Thematic analysis was used to identify key themes and patterns within the data. Findings and Discussion: The findings indicate that midwifery-led care models significantly improve maternal and neonatal outcomes by providing continuous, personalized support, which reduces unnecessary medical interventions and enhances maternal satisfaction and emotional well-being. The study also emphasizes the importance of cultural competence in midwifery, as culturally sensitive care fosters trust and enhances health outcomes. Integrating midwifery into national health systems, supported by appropriate policies and resources, is crucial for achieving better maternal and neonatal health outcomes. The research highlights the need to address socio-economic barriers that hinder effective midwifery care in low-resource settings. Implications: The study provides valuable insights for policymakers and healthcare providers, underscoring the importance of supportive policies, adequate resources, and ongoing professional development for midwives. Countries can enhance maternal and neonatal health outcomes by integrating midwifery services into national health systems and fostering cultural competence. The findings also suggest areas for future research, including the need for more diverse settings and mixed-method approaches to provide a comprehensive understanding of midwifery practices.